Cognitive and neurobehavioral patterns in a sample of Egyptian patients genetically diagnosed with Duchenne muscular dystrophy - Maha Mohamed Sayed; Nagia Aly Fahmy; Mahmoud Mamdouh Mohamed El Habiby; Nermine Salah Eldin Elsayed; Sara Mohamed Kamal Mohamed El Bukhari; Rehab Mohamed Naguib (Middle East Current Psychiatry, 2022)
Abstract Background Children with Duchenne muscular dystrophy report a higher rate of cognitive and psychiatric disorders relative to general population. This study will describe and compare the psychiatric and cognitive problems in DMD patients with healthy controls. Results A statistically significant difference was found between the case and control groups regarding Total IQ (TIQ) with a mean of (82 ± 16) in cases compared to (94 ± 10) in controls, in which 58% of DMD boys had <90 TIQ and 40% less than 70. We also found that 58% of cases have delayed onset of speech, 38% have attention-deficit/hyperactivity disorder, 6% have autism spectrum disorder, 14% have anxiety disorders, and 22% have major depressive disorder. Ninety-two percent of cases had deletion mutations. Conclusions According to our results, we conclude that boys with DMD had a lower Total IQ and higher rate of psychiatric disorders than the general population. Also, school attendance and speech development are more affected in DMD patients compared to controls, with more speech delay and dropping out of school. So, the authors of this study recommend establishing cognitive and psychiatric screening as a routine in the evaluation and follow-up of DMD children.